Development of Non-linear Two-Terminal Mass Components for Application to Vehicle Suspension Systems - Yang, Shuai (Université d'Ottawa / University of Ottawa, 2017)
To achieve passive vibration control, an adaptive flywheel design is proposed and fabricated from two different materials. The corresponding mathematical models for the adaptive flywheels are developed. A two-terminal hydraulic device and a two-terminal inverse screw device are introduced to analyze the two adaptive flywheels. Experiments are carried out to identify key parameters for both the two-terminal hydraulic system and the inverse screw system. The performance of three different suspension systems are evaluated; these are the traditional suspension system, the suspension system consisting of an ideal two-terminal device with constant flywheel and the suspension system consisting of an ideal two-terminal device with an adaptive flywheel (AFW suspension system). Results show that the AFW suspension system can outperform the other two suspension systems under certain conditions. The performance of a suspension system with the adaptive flywheel under different changing ratio is evaluated, and an optimal changing ratio is identified under certain circumstances. To obtain the steady-state response of the two-terminal device with adaptive flywheel, three different methods have been applied in this thesis. These methods are the single harmonic balance method, the multi-harmonic balance method and the scanning iterative multi-harmonic balance method, respectively. Compared to the single harmonic balance method, the multi-harmonic balance method provides a much more accurate system response. However, the proposed scanning iterative multi-harmonic balance method provides more accurate system response than the single harmonic balance method with much less computational effort.
Keywords: Two-terminal; Non-linear; Adaptive flywheel; Car suspension